2422. Efficacy of Cefoxitin for the Treatment of Urinary Tract Infection (UTI) Due to ESBL-Producing E. coli and K. pneumoniae Isolates. (26th November 2018) - Senard, Olivia; Bouchand, Frederique; Deconinck, Laurene; Matt, Morgan; Fellous, Lesly; Rottman, Martin; Perronne, Christian; Dinh, Aurelien; Davido, Benjamin
Abstract: Background: Cefoxitin has a good in vitro activity and stability in resistance to hydrolysis by ESBLs, and is a good candidate for the treatment of urinary tract infection (UTI). However, data are scarce regarding its use in clinical practice, especially against K. pneumoniae deemed to be capable of the acquirement of porin-deficient mutant. Methods: We conducted a retrospective study from September 2014 to November 2017, in a tertiary-care hospital. We gathered all prescriptions of Cefoxitin for UTI due to ESBL isolates. We compared the clinical outcomes between E. coli and K. pneumoniae ESBL-producing isolates after a 90-day follow-up. When available, we assessed whether Cefoxitin-based regimen was associated with an emergence of resistance. To our knowledge there is no clinical data supporting a real threat of development of resistance in UTI. Results: The treatment of 31 patients with a mean age of 60 ± 18 years was analyzed. We observed a clinical cure at D90 in 81.2% ( n = 13/16) of cases for ESBL E. coli isolates and 85.7% (12/14) for ESBL K. pneumoniae ( P = 0.72). Overall, we noted an efficacy of FOX around 83.3% ( n = 25/30). Median dose of Cefoxitin was 4 g (2–8). Only one patient infected by an ESBL E. coli received an oral relay with levofloxacin for 4 additional days. No adverse events were reported. One patient who relapsed, carried a K. pneumoniae isolate that became intermediate to Cefoxitin in the follow-up. Conclusion: In a period of major threat with a continuous increase of ESBL obliging to a policy of carbapenem-sparing regimens, it seems detrimental to deprive physicians of using Cefoxitin for ESBL Enterobacteriaceae for the treatment of UTI while our data show its efficacy. Disclosures: All authors: No reported disclosures.